2008
DOI: 10.1002/mnfr.200700258
|View full text |Cite
|
Sign up to set email alerts
|

The potential of sphingomyelin as a chemopreventive agent in AOM‐induced colon cancer model: wild‐type and p53+/– mice

Abstract: A protective effect of sphingolipids on colorectal cancer (CRC) has been reported in certain mouse strains. It is unknown if sphingolipids are protective in a p53 deficiency mouse model of CRC. This study investigated the effect of sphingomyelin (SM) on intestinal sphingomyelinase (SMase) activity, colonic epithelial biology and azoxymethane (AOM)-induced CRC. Groups of wild-type (C57BL/6J) and p53+/- mice were fed 0.1% SM diet for 4 wk, administered a single AOM injection and then killed 6 h later to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…(174), only 2% of p53 +/− mice developed intestinal adenocarcinomas and p53 −/− mice failed to develop intestinal tumors. p53 null mice do develop increased numbers of intestinal tumors when treated with carcinogens, such as AOM (175,176,177) and DMH (178). In addition, p53 null genotypes increase susceptibility to intestinal tumorigenesis driven by inflammation (179) or Apc mutation (180).…”
Section: Animal Models Of Human Colorectal Cancermentioning
confidence: 99%
“…(174), only 2% of p53 +/− mice developed intestinal adenocarcinomas and p53 −/− mice failed to develop intestinal tumors. p53 null mice do develop increased numbers of intestinal tumors when treated with carcinogens, such as AOM (175,176,177) and DMH (178). In addition, p53 null genotypes increase susceptibility to intestinal tumorigenesis driven by inflammation (179) or Apc mutation (180).…”
Section: Animal Models Of Human Colorectal Cancermentioning
confidence: 99%
“…Reed et al 21 reported in 2008 that p53 knockout animals did not develop colorectal neoplasias; however, the association of APC min and p53 knockout mutations promoted an increase in aberrant crypts foci number when compared to APC min animals. In addition, in 2008 Hu et al 10 reported that an association of p53 knockout animals with tumor inducer AOM was efficient in inducing carcinogenesis in the colon of the animals, and also to potentiate the action of the AOM. The same could be observed by Sakai et al 22 in which p53 knockout animals showed only neoplastic development when placed in contact with the DMH inducer.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the effects of dietary SM in the context of p53 deficiency, wild-type and p53 mutant mice were treated with AOM to investigate the relationship between SM feeding and the tumor suppressor gene p53. The results indicated that a 0.1% SM diet for 4 weeks inhibited cell proliferation but did not induce apoptosis in the distal colon of both types of AOM-treated mice [57]. Feeding of a 0.05% SM diet for 33-38 weeks also suppressed cell proliferation in the distal colon and tumor.…”
Section: Sphingomyelinmentioning
confidence: 87%